2021
DOI: 10.7717/peerj.11776
|View full text |Cite
|
Sign up to set email alerts
|

The effects of genetic drift and genomic selection on differentiation and local adaptation of the introduced populations of Aedes albopictus in southern Russia

Abstract: Background Asian tiger mosquito Aedes albopictus is an arbovirus vector that has spread from its native habitation areal in Southeast Asia throughout North and South Americas, Europe, and Africa. Ae. albopictus was first detected in the Southern Federal District of the Russian Federation in the subtropical town of Sochi in 2011. In subsequent years, this species has been described in the continental areas with more severe climate and lower winter temperatures. Methods Genomic analysis of pooled Ae. albopictu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…in Southern Russia, but heavily restricted gene flow or population exchange is reported between the different study sites (Konorov et al, 2021). The weak genetic structure, high levels of admixture, and lack of IBD found in this study for Ae.…”
Section: Genetic Assignment Testmentioning
confidence: 46%
See 1 more Smart Citation
“…in Southern Russia, but heavily restricted gene flow or population exchange is reported between the different study sites (Konorov et al, 2021). The weak genetic structure, high levels of admixture, and lack of IBD found in this study for Ae.…”
Section: Genetic Assignment Testmentioning
confidence: 46%
“…In Ae. albopictus , reports of very high levels of differentiation among samples of recently invading populations at regional levels have been identified in Southern Russia, but heavily restricted gene flow or population exchange is reported between the different study sites (Konorov et al, 2021 ). The weak genetic structure, high levels of admixture, and lack of IBD found in this study for A e. albopictus suggest rapid expansion most likely through human‐aided dispersal along transportation routes across the Alps.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic dynamics of Ae. albopictus populations have been driven by multiple introductions, genetic drifts and founder effects during their invasion process (Gao et al, 2021; Hall et al, 2022; Konorov et al, 2021; Latreille et al, 2019). The weak gregarine diversity (limited density of gregarines from Otu000002 and Otu000003) in recently introduced populations could then be related to those events since the parasite cannot reproduce outside of its host.…”
Section: Discussionmentioning
confidence: 99%
“…Our conclusions are also supported by the results of the analysis of the genomes of individuals from Sochi and Krasnodar cities (Cfa zone), which showed that despite significant differences in the allele frequency spectrum, Ae. albopictus from Sochi and Krasnodar were closely related, had a common origin and formed a clade related to mosquitoes from Italy and Greece ( 42 ). The lack of genetic structure or isolation by distance were observed in many studies on Ae.…”
Section: Discussionmentioning
confidence: 99%